2017
DOI: 10.22192/ijcrms.2017.03.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the relation of BMI with dysmenorrhea in adolescents girls

Abstract: Introduction: Adolescence is the segment of life between 10-19 years of age. Dysmenorrhea refers to a cyclical lower abdominal or pelvic pain occurring during menstruation which may radiate to the back or to the thighs. It is necessary to clarify what factors are associated with menstrual pain in adolescence, to assist in improving quality of life. The present study was conducted to see the relation of BMI with dysmenorrhea. Aims &Objectives: To record the Body Mass Index (BMI) of the adolescents and statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Moreover, Kaur et al, reported a signi cant relation between severe dysmenorrhea, and BMI especially (underweight and overweight adolescents) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kaur et al, reported a signi cant relation between severe dysmenorrhea, and BMI especially (underweight and overweight adolescents) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown different results regarding the relationship between nutritional status/Body Mass Index (BMI) and dysmenorrhea (Mohapatra et al, 2016). One of the results of the study states that nutritional status is the dominant factor affecting dysmenorrhea, respondents with overweight nutritional status have higher chance of experiencing dysmenorrhea compared to those with normal nutritional status (Kaur et al, 2017). Other statements also argue that there is no relationship between BMI and dysmenorrhea (Wahyuni et al, 2018).…”
Section: The Effect Of Body Mass Index (Bmi) On Primary Dysmenorrheamentioning
confidence: 95%
“…Ju et al [24] observed an increased risk of dysmenorrhea in both underweight and obese individuals, while Jiang et al [25] reported an increased odds of dysmenorrhea in women with either lower or higher BMI. Furthermore, Gurdip et al [26] identified a significant relationship between dysmenorrhea and underweight or overweight women. The controversial relationship between BMI and PD explains why underweight and overweight adolescents were excluded from this study.…”
Section: Relationship Between Dysmenorrhea and Bmimentioning
confidence: 99%